Banking on Health : The World Bank and Health Sector Reform in Latin America - Noy, Shiri (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book addresses the puzzle of why the World Bank was unable to effect sweeping neoliberal health reforms in Latin America from the 1980s onward. Through the use of quantitative regional data together with interview and archival data collected during fieldwork in Argentina, Costa Rica, Peru, and Washington DC, this book argues that the answer to this puzzle is twofold. First, the World Bank has not promoted a uniformly neoliberal, monolithic agenda in health. Second, countries' autonomy and capacity in this sector shape how the World Bank is involved in reforms. Finally, the book distinguishes neoliberal ends from means in health sector reform and traces changes in "banking on health" over time.
Keywords: Social sciences.; Public health.; International economics.; Health economics.; Medical economics.; Development economics.; Political sociology.; elektronické knihy; electronic books